2021
DOI: 10.1038/s41398-021-01227-8
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprogressive nature of major depressive disorder: evidence from an intrinsic connectome analysis

Abstract: Major depressive disorder (MDD) is a prevailing chronic mental disorder with lifetime recurring episodes. Recurrent depression (RD) has been reported to be associated with greater severity of depression, higher relapse rate and prominent functioning impairments than first-episode depression (FED), suggesting the progressive nature of depression. However, there is still little evidence regarding brain functional connectome. In this study, 95 medication-free MDD patients (35 with FED and 60 with RD) and 111 matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 56 publications
4
27
0
Order By: Relevance
“…Previous studies have found reduced FC in the DMN, dorsal attention network, and somatomotor network in the FDE group compared with the recurrent depression (RD) group, suggesting possible FC hypoconnectivity in multiple brain networks in the FDE group ( 34 ). In this study, we used a seed-based FC approach to systematically compare FC abnormalities in the DMN, CCN, and AN in RDE patients, FDE patients, and HCs.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous studies have found reduced FC in the DMN, dorsal attention network, and somatomotor network in the FDE group compared with the recurrent depression (RD) group, suggesting possible FC hypoconnectivity in multiple brain networks in the FDE group ( 34 ). In this study, we used a seed-based FC approach to systematically compare FC abnormalities in the DMN, CCN, and AN in RDE patients, FDE patients, and HCs.…”
Section: Introductionmentioning
confidence: 88%
“…MDD has also been studied previously using a combination of several networks, including adolescent depression or TRD ( 23 , 30 34 ). Most studies have focused on FC abnormalities in the DMN, CCN, and AN in MDD patients ( 29 , 30 , 32 34 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that cerebral NAA concentrations should be lower in MDD patients relative to HC. Our hypothesis is that NAA reduction will be larger in cMDD as compared to FED, in accordance with progressive neuronal damage or hypometabolic changes over the course of the illness(3).…”
Section: Introductionmentioning
confidence: 97%
“…In MDD, a malfunction of multiple brain areas, including the limbic system and the prefrontal cortex, has been postulated, but, despite significant advances, its pathophysiology and the molecular basis of treatments are still poorly understood. This is further complicated by the heterogeneity of disease phases, as clinical(2) and radiological(3) markers differ between First Episode of Depression (FED) and chronic MDD (cMDD). Differentiating MDD stages has important implications for patient care and clinical research(4).…”
Section: Introductionmentioning
confidence: 99%